The Influence of Macroeconomics on the Share Price of the Energy Sector Listed on the Indonesian Stock Exchange - Vanny Rahma Yulianti; Rusdi Hidayat Nugroho (Universitas KH. Abdul Chalim Mojokerto, 2025)
The economy plays a vital role in a country's ability, in the era of globalization economic strength determines the country's international competitiveness, including involvement in global trade. The capital market is an important element in the economy, providing funding for companies for business expansion and can encourage people to manage their finances in the form of stock investment. The uncertainty in stock prices encourages investors to need information as a basis for decision making. This study aims to determine the effect of world oil prices, interest rates, rupiah exchange rates, and foreign direct investment on energy sector stock prices on the Indonesia Stock Exchange. This study uses an associative method with a quantitative approach using secondary data. The research population was 88 companies. Sampling using purposive sampling technique so as to obtain 24 companies. The research data is in the form of monthly time series data from January 2019 to December 2023 as much as 60 data. Secondary data was analyzed using the classical assumption test and multiple linear regression analysis techniques supported by SPSS software. The simultaneous test results state that world oil prices, interest rates, rupiah exchange rates, and foreign direct investment have a significant positive effect on energy sector stock prices. Partial test results state that world oil prices, interest rates, rupiah exchange rates, and foreign direct investment have a significant positive effect on energy sector stock prices.